2014
DOI: 10.1259/bjr.20130511
|View full text |Cite
|
Sign up to set email alerts
|

Acute adverse reactions to iopromidevsiomeprol: a retrospective analysis of spontaneous reporting from a radiology department

Abstract: Comparative studies of media contrast safety are scarce and summary information on product characteristics is insufficient. This study showed the differences in severity and profile of adverse reactions between iopromide and iomeprol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…[5][6][7] However, with the introduction of nonionic low-osmolality ICM, the reported frequency of vomiting has declined with varying range, from 1% or less to 11.7%, lessening the rationale of the fasting. 1,5,[8][9][10][11] Although nearly all radiological clinics in industrial countries only use non-ionic ICM, the current preparatory fasting policy regarding fasting duration and content (solids or fluids) varies considerably across hospital and a 4-6 h fasting is one of the most common fasting policies. 1,12 Furthermore, fasting duration before CT examination was heterogeneous across countries, with a tendency of longer fasting duration in Korea than in Europe.…”
mentioning
confidence: 99%
“…[5][6][7] However, with the introduction of nonionic low-osmolality ICM, the reported frequency of vomiting has declined with varying range, from 1% or less to 11.7%, lessening the rationale of the fasting. 1,5,[8][9][10][11] Although nearly all radiological clinics in industrial countries only use non-ionic ICM, the current preparatory fasting policy regarding fasting duration and content (solids or fluids) varies considerably across hospital and a 4-6 h fasting is one of the most common fasting policies. 1,12 Furthermore, fasting duration before CT examination was heterogeneous across countries, with a tendency of longer fasting duration in Korea than in Europe.…”
mentioning
confidence: 99%
“…Severe hypersensitivity reactions were between 0.010 and 0.024%, with anaphylaxis being the most frequent reaction (Table I) (9,10,18). Regarding the skin patterns observed in these cases, the most frequent were urticaria (between 30.77 and 83.78% of the cases with skin manifestations) (10,13,15,1719), rash (38.46–85.3%) (9,10,13,19), itching sensation/pruritus (12.82–100%) (10,1315,1719), oedema (6.25–17.3%) (12,18,19), erythemas (36.54–100%) (12,14,1719), angioedema (8%-13.51%) (15,17), and angioneurotic oedema (3.84%) (18) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The female sex was associated with increased risk for immediate allergic reactions to ICM between 51.44 and 65.95% (9,10,14,15,17,18). Other risk factors identified included history of previous reactions to ICM (1.2–11.6%) (9,1215,17), atopy (14.3%) (8), asthma (2.1–12.7%) (9,14,15,17), drug allergy (3.6–25%) (9,14,15,17), and allergic rhinitis (1.5–4%) (14,15,17).…”
Section: Resultsmentioning
confidence: 99%
“…Commonly reported adverse reactions associated with iopromide use include nausea, vomiting, headache and diverse allergic reactions, although severe adverse reactions like anaphylaxis are rare [35]. Additional studies have revealed other specific adverse reactions associated with iopromide use, including contrast-induced nephropathy (CIN), skin vasculitis [35] and colitis. [35][36][37][38][39].These studies highlight the importance of careful monitoring for adverse reactions associated with iopromide use in clinical practice.…”
Section: Iopromide Adverse Events Assessmentmentioning
confidence: 99%